2021
DOI: 10.1088/1755-1315/934/1/012091
|View full text |Cite
|
Sign up to set email alerts
|

Acceleration of Sago Food Diversification in Improving the Welfare of Sago Farmers in Riau Province

Abstract: There have been many efforts to increase agricultural productivity as a step to improve farmers’ welfare, one of which is through food diversification. Processing sago into various kinds of processed food products is a strategic to accelerate sago diversification. The market potential for sago starch in Riau Province is quite growing along with the local food products development. The purpose of this study was to analyze practical steps as an acceleration of sago food diversification so that opportunities coul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Research into local production has focused on the attitudes and priorities of farmers who directly produce sago [24]. There is a research gap regarding the opinions of other supply chain actors and interested stakeholders in West Papua.…”
Section: Introductionmentioning
confidence: 99%
“…Research into local production has focused on the attitudes and priorities of farmers who directly produce sago [24]. There is a research gap regarding the opinions of other supply chain actors and interested stakeholders in West Papua.…”
Section: Introductionmentioning
confidence: 99%
“…Research into local production has focused on the attitudes and priorities of farmers who directly produce sago, which indicated that diversification of sago products within this supply chain has beneficial economic consequences for primary producers [ 27 ]. There is a research gap regarding the opinions of other supply chain actors and interested stakeholders in West Papua.…”
Section: Introductionmentioning
confidence: 99%